Conveyor belt control by programmable logic controller / Shamsudin Ismail and Abd. Hafidz Hamzah - Ismail, Shamsudin; Hamzah, Abd. Hafidz (1990)
This project is about the application of Programmable Logic- Controller (PLC) in controlling the sequence of a conveyor system. In order to design a good system, a study of ;the characteristic of the PLC and the equipments used is required. The ladder diagram and ladder logic have been developed. The ladder logic then was installed into the PLC to control the sequence of the conveyor system model.